PENGEMBANGAN MINAT DAN BAKAT SISWA DI MIN 1 KOTA MALANG - Nadia, Nuril (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2024)
This study aims to explore the development of students' interests and talents at MIN 1 Malang City through a qualitative approach, focusing on the methods used by teachers and the school environment to nurture students' potential. Data were collected through in-depth interviews with teachers, students, and parents, allowing for a comprehensive understanding of the strategies and challenges faced in this process. The qualitative method was chosen to gain detailed insights into the experiences and perceptions of stakeholders in the education system at MIN 1 Malang City. The interviews revealed various factors influencing the development of students' interests and talents, including the availability of extracurricular activities, teacher support, parental involvement, and the school’s commitment to personalized education. Furthermore, challenges such as limited resources and time constraints were identified as obstacles to fully optimizing student potential. The study concludes that a collaborative approach involving teachers, parents, and the school management is essential in fostering student development, and that ongoing evaluation and adaptation of programs are necessary to address the evolving needs of students.